Pengaruh pemupukan dan padat penebaran terhadap tingkat kelangsungan hidup dan pertumbuhan post larva udang vaname (Litopenaues vannamei) - Ernawati; Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2017)
The aim of this research is to know the effect of fertilization and density on survival rate and the absolute growth of post-larvae of shrimp vanname (Litopenaeus vannamei). The study was conducted from 18 August to 5 September 2013 at Oensuli ponds, Kabangka, Muna Regency, Indonesia. The research used animal test of vaname shrimp stadium PL6, a fertilizer of Urea and TSP. The study used styrofoam container, 75 cm long, 37 cm wide, and 27 cm high. Research using Factorial RAL, fertilization and density used three levels, three replications, so that the experiment of 27 units. The fertilizer treatment consisted of no-fertilizer (Control), combination Urea 0.5 g/TSP 0.7 g (P2), combination Urea 0.7 g/TSP 0.9 g (P3). The density treatment consists of density 9 ind/container (Control), density 14 ind/container (KP2) and density 19 ind/container (KP3). Parameters observed survival rate (SR) and absolute growth (G). Data analysis using ANOVA (a0,05) with IBM SPSS Statistic 22. The results showed that fertilization and stocking density had a significant effect on survival and post larvae growth of vaname shrimp. The optimum use of 0.7 g/TSP 0.9 g urea per container. The optimum fertilizer composition of growth was Urea 0.5 g/TSP 0.7 g per container. The best survival rate through a combination of Urea 0.7 g/TSP 0.9 g, density 9 ind per container, equivalent Urea 26 kg/TSP 33 kg density 333.000 ind per ha. The best growth through a combination of Urea 0.5 g/TSP 0.7 g, density 9 ind per container or Urea 19 kg/TSP 26 kg, density 333.000 ind per ha.